The Intrinsic Link Between Food Allergy and Allergic Rhinitis : A Family Medicine Perspective on Atopic March and Persistent Nasal Symptoms - Hidayati, Nurul; Dwi Rahayu, Indriati; Rizki Fauzi, Muhammad (Jurnal Ilmu Kedokteran Keluarga, 2025)
Allergic rhinitis (AR) is a prevalent chronic respiratory condition, yet its intricate connection with food allergy (FA) is often underappreciated in clinical practice. This paper examines the "atopic march", the natural progression of allergic diseases, through a case study that highlights the significant interplay between a patient's food allergy history and the manifestation of persistent, moderate-to-severe allergic rhinitis, emphasizing the crucial role of family medicine in comprehensive patient assessment. We present a case of a 25-year-old male experiencing persistent nasal congestion, rhinorrhea, and sneezing for a year, exacerbated by environmental triggers. Notably, he reported a resolved childhood seafood allergy. His family history revealed a strong pattern of atopy, with his mother having similar allergic rhinitis and seafood allergy, and his elder sister presenting with asthma and seafood allergy. This familial predisposition for both food and inhalant allergies strongly suggests an underlying atopic diathesis. This patient's presentation vividly illustrates the complex relationship between early-life food sensitization and the subsequent development of allergic rhinitis. While his childhood seafood allergy had clinically resolved, the underlying IgE-mediated immune response likely contributed to his sustained hyper-responsiveness, predisposing him to AR. The strong familial aggregation of both food and respiratory allergies underscores the genetic contribution to the atopic march. Management involved a comprehensive approach, including pharmacological interventions and environmental control, but crucially, also emphasized the importance of recognizing the historical and familial links to food allergies in understanding the patient's current rhinitis picture. Further investigation, such as specific IgE testing or skin prick tests, would be beneficial to identify any lingering or new food sensitivities that might contribute to his nasal symptoms. This case powerfully demonstrates that allergic rhinitis should not be viewed in isolation from a patient's broader allergic history, particularly early-life food allergies. A comprehensive family medicine approach that considers the full spectrum of atopic manifestations, including past and familial food allergies, is essential for a complete understanding, effective management, and improved long-term outcomes in patients with persistent allergic rhinitis.